Foraging and mobility in three species of Aciculata (Annelida: Polychaeta) - Pardo,E. V. (2006)
Aspects of feeding, such as food capture and ingestion, as well as mobility of the polychaetes Eurythoe complanata, Marphysa formosa and Diopatra aciculata, from São Sebastião Channel (São Sebastião, state of São Paulo) were observed in laboratory conditions. Eurythoe complanata, a carnivorous species, fed exclusively on pieces of fish with the aid of strong muscular retractable lips, and detected the presence of food by chemical stimuli. Diopatra aciculata, an omnivorous species, captured and ingested different kinds of food with the aid of its jaws, generating a flow of water through its tube by which it detects the presence of food and oxygenates its gills. Marphysa formosa also used its jaws to bite and lacerate food. These species showed greater or lesser degrees of intolerance to light.